2017
DOI: 10.1037/fam0000310
|View full text |Cite
|
Sign up to set email alerts
|

Harsh parenting, child behavior problems, and the dynamic coupling of parents’ and children’s positive behaviors.

Abstract: We examined self-reported maternal and paternal harsh parenting (HP) and its effect on the moment-to-moment dynamic coupling of maternal autonomy support and children’s positive, autonomous behavior. This positive behavior coupling was measured via hidden Markov models as the likelihood of transitions into specific positive dyadic states in real time. We also examined whether positive behavior coupling, in turn, predicted later HP and child behavior problems. Children (N=96; age 3½ years at Time 1) and mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 53 publications
2
73
0
1
Order By: Relevance
“…This protects them from getting into internalizing problems. A recent study also found that maternal autonomy support at time 1 predicted fewer internalizing problems for children at time 2 (Lunkenheimer, Ram, Skowron & Yin, ).…”
Section: Discussionmentioning
confidence: 89%
“…This protects them from getting into internalizing problems. A recent study also found that maternal autonomy support at time 1 predicted fewer internalizing problems for children at time 2 (Lunkenheimer, Ram, Skowron & Yin, ).…”
Section: Discussionmentioning
confidence: 89%
“…Relations between negative parenting responses and child internalizing symptoms have also been demonstrated. Greater maternal negative affectivity (Fang & Gagne, ), and less autonomy support (Lunkenheimer, Ram, Skowron, Peifeng, & Yin, ) and sensitivity (Kok et al, ) have been associated with more internalizing symptoms among preschoolers. However, these effects tend to be small (McLeod, Weisz, & Wood, ), are not consistent across studies (Kopala‐Sibley et al, ), and provide little support for child effects (Hipwell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The highly emotional reaction of parents and their threats of harsh punishment limits the adolescents' management of their own behaviour, echoes ineffective role modelling of the part of the parent, and raises the possibility of engagement in delinquent behaviour (Lunkenheimer, Ram, Skowron & Yin, 2017;Ross & Howe, 2009). It is noted that the emotional feelings of the adolescent are linked to the nature of the parent-adolescent relationship, the family environment and delinquent behaviour of the adolescent (Soloski & Berryhill, 2015).…”
Section: Do Not Really Feel Happy About It Because Then I Have To mentioning
confidence: 99%